Analysis of Child Sexual Violence Factors in Indonesia Using Bronfenbrenner's Ecological Approach: Systematic Literature Review: Analisis Faktor Kekerasan Seksual Anak di Indonesia Melalui Pendekatan Ekologi Bronfenbrenner: Systematic Literature Review - BRYAN ANDIKA; Mary Philia Elisabeth (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Child sexual violence is a complex and multidimensional violation of human rights, involving interactions among individual, familial, community, and broader social systems. This study aims to analyze the risk factors and protective factors of child sexual violence in Indonesia using Bronfenbrenner’s ecological theory framework through a systematic literature review approach. Data were collected using the SPIDER method from the Garuda database, employing the keywords “child sexual violence” and “causes,” covering publications from 2017 to 2025. Out of 140 identified articles, 16 met the eligibility criteria and were analyzed thematically. The findings indicate that dominant risk factors are primarily located at the microsystem level, including inadequate parental supervision, permissive parenting styles, and limited sexual education. At the exosystem level, significant risk factors include low socioeconomic conditions, exposure to pornography, and high-risk social environments. Meanwhile, protective factors were identified mainly at the macrosystem level, such as legal regulations and public awareness campaigns, as well as at the chronosystem level, particularly adaptive policy changes responding to social and technological developments. The analysis further reveals that interactions across ecological system levels are dynamic, where vulnerabilities at one level may amplify risks at other levels. This study emphasizes that child sexual violence should be understood as a systemic phenomenon resulting from interconnected ecological factors, requiring integrated, multi-level interventions. The findings are expected to contribute to the development of more proactive, collaborative, and sustainable ecology-based prevention strategies for addressing child sexual violence in Indonesia.